Mamma Mia, A Singable Translation! - Andrej Stopar (ELOPE, 2016)
The article discusses and analyzes approaches to translating singable texts. It presents a linguistic (prosodic, lexical and structural) analysis of the Slovenian translation of the musical Mamma Mia! The aim of the qualitative and quantitative study is to investigate the translation strategies used to produce a singable target text. The results of the analysis suggest that producing a prosodic match is a basic requirement, whereas the lexical, structural and/or poetic characteristics of the source text are subject to changes. Overall, the findings show that the function and the purpose of the translation play a crucial role in the prioritization of translation strategies.